The “Spirit of Bandung” 1955–1985: Thirty years since the Bandung Conference - Volker Matthies (Intereconomics, 1985)
On 24th and 25th April, 1985, delegates from more than 80 Asian and African countries gathered in the Indonesian city of Bandung at the “Gedung Merdeka”, or “House of Freedom”, to commemorate the famous Bandung Asian-African Conference held thirty years previously. What, in retrospect, has been the historical and political significance of Bandung? What have been the achievements of its heirs so far?
Keywords: 330; Group of 77